Pengaruh Budaya Organisasi Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Disnakertrans Kabupaten Karawang - Nandang Nandang; Asep Jamaludin; Deby Permadani (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to determine the effect of organizational culture and work discipline on employee performance at the Karawang Regency Manpower and Transmigration Office. This research uses quantitative, descriptive, and verification methods. The population and sample of this study were 100 employees at the Office of Manpower and Transmigration, Karawang Regency. SPSS 21 software is used to test the hypothesis in this study. The results of this study found that organizational culture has a partial effect on employee performance with a tcount of 7.062 and a ttable of 1.988 where the tcount value of organizational culture is greater than ttable and the sig value obtained is 0.000 which is still below 0.05. And work discipline has a partial effect on employee performance with a tcount of 2.834 and a ttable of 1.988 where the tcount value of work discipline is greater than the ttable and the sig value obtained is 0.006 which is below 0.05. As well as organizational culture and work discipline simultaneously influence employee performance with a ftable value of 35.368 and a ftable of 3.089 where the fcount value is greater than ftable and the sig value obtained is 0.000 where the sig level is below 0.05, which means the influence of organizational culture and work discipline very significant effect on employee performance. Keywords: Organizational Culture, Work Discipline, Employee Performance.